Synthesis, Characterization, Thermal Properties and Flame Retardance of Aromatic Polyimides Containing Halogen and Phosphorus Components - A. Mutar*, Mohammed; O. Mutashar, Mahmood (Asian Journal of Chemistry, 2014)
Several systematically varied aromatic polyimides were prepared by solution polycondensation reaction of different dianhydrides (pyromellitic dianhydride), 3,3'4,4'-benzophenone tetra-carboxylic dianhydride and 4,4'-hexafluoroisopropylidenebis(phthalic anhydride), with various structurally different diamines containing halogens and phosphorus components using a standard two-stage process with thermal imidization of poly(amic acid). Chemical structures, of these materials were characterized with FT-IR, NMR, elemental analysis. Thermal analysis of thermal gravimetricanalysis (TGA) reveals that these resulted aromatic polyimides (P1-P4) possess thermal stability. Furthermore, high char yields in TGA analysis values indicate that these halogens and phosphorus containing aromatic polyimidespossess excellent flame retardant properties.